2019
DOI: 10.1001/jama.2019.11645
|View full text |Cite
|
Sign up to set email alerts
|

N95 Respirators vs Medical Masks for Preventing Influenza Among Health Care Personnel

Abstract: IMPORTANCE Clinical studies have been inconclusive about the effectiveness of N95 respirators and medical masks in preventing health care personnel (HCP) from acquiring workplace viral respiratory infections.OBJECTIVE To compare the effect of N95 respirators vs medical masks for prevention of influenza and other viral respiratory infections among HCP. DESIGN, SETTING, AND PARTICIPANTSA cluster randomized pragmatic effectiveness study conducted at 137 outpatient study sites at 7 US medical centers between Septe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
419
0
35

Year Published

2019
2019
2020
2020

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 456 publications
(467 citation statements)
references
References 33 publications
(56 reference statements)
6
419
0
35
Order By: Relevance
“…A randomized clinical trial has reported that the N95 respirators vs medical masks resulted in no significant difference in the incidence of laboratory confirmed influenza [4]. In our study, we observed that the N95 respirators, disinfection and hand washing appeared to help reduce the infectious risk of 2019-nCoV in doctors and nurses.…”
mentioning
confidence: 44%
“…A randomized clinical trial has reported that the N95 respirators vs medical masks resulted in no significant difference in the incidence of laboratory confirmed influenza [4]. In our study, we observed that the N95 respirators, disinfection and hand washing appeared to help reduce the infectious risk of 2019-nCoV in doctors and nurses.…”
mentioning
confidence: 44%
“…A randomized clinical trial has reported N95 respirators vs medical masks as worn by participants in this trial resulted in no significant difference in the incidence of laboratory confirmed influenza. 4 In our study, we found N95 respirators, disinfection and hand washing can help to reduce the risk of 2019-nCoV infection in medical staffs. Interestingly, department with a high proportion of male doctors seem to have a higher risk of infection.…”
Section: Suspicious Cases Of 2019-ncov Infection Wasmentioning
confidence: 63%
“…RCTs comparing N95 respirators to medical masks in health care personnel working in outpatient and ward settings have not shown significant differences in protection from laboratory-confirmed influenza or other RVIs [72,73]. The relevance of these observations to the ICU setting is uncertain, given the frequent use of aerosol-generating procedures in critically ill patients.…”
Section: Infection Prevention and Controlmentioning
confidence: 99%